Application of BO-BiGRU based post equalizer in high-speed underwater visible light communication system - Haoyu ZHANG; Li YAO; Chaoxu CHEN; Jianyang SHI; Chao SHEN; Nan CHI (Dianxin kexue)
Signals are susceptible to nonlinear effects in the process of underwater visible light communication (UVLC) channel transmission.In order to improve the communication performance of the system, it is very important to recover the received signals.A bidirectional gated recurrent unit model based on Bayesian optimization algorithm (BO-BiGRU) was proposed as post equalizer in UVLC system, which could automatically find the optimal hyperparameters.BO-BiGRU model was applied to the 1.2 m underwater experimental platform.64 quadrature amplitude modulation (QAM)-carrierless amplitude-and-phase modulation (CAPM) was adopted, and 3.10 Gbit/s rate of data transfer was achieved under the condition that the bit error ratio (BER) of the system was less than 3.8×10-37% forward error correction (FEC), which is 128 Mbit/s higher than the traditional post equalization method.